A Convenient Synthesis by Microwave Assisted High-Speed and Antibacterial Activity of Ethyl-4-aryl-6-methyl-2-oxo (or thioxo)-1,2,3,4-tetrahydropyrimidine-5-Carboxylate Derivatives without Solvent - Foroughifar, N.; Mobini Khaledi, A.; Shariatzadeh, S.M.; Masoudnia, M. (Asian Journal of Chemistry, 2010)
Ethyl 4-aryl-6-methyl-2-oxo (or thioxo)-1,2,3,4-tetrahydropyrimidine-5-carboxylate 4(a-h) and 4-aryl-2-oxo (or thioxo)-1,2,3,4-tetrahydropyrimidine 6(a-c) were synthesized under reflux and microwave-promoted without solvent and high-speed. These compounds were screened for antifungal and antibacterial activities test organisms.